Discovery of radio jets in the Phoenix galaxy cluster center. (27th May 2020) - Akahori, Takuya; Kitayama, Tetsu; Ueda, Shutaro; Izumi, Takuma; Lee, Kianhong; Kawabe, Ryohei; Kohno, Kotaro; Oguri, Masamune; Takizawa, Motokazu
Abstract: We report the results of the Australia Telescope Compact Array (ATCA) 15 mm observation of the Phoenix galaxy cluster possessing an extreme star-burst brightest cluster galaxy (BCG) at the cluster center. We spatially resolved radio emission around the BCG, and found diffuse bipolar and bar-shape structures extending from the active galactic nucleus (AGN) of the BCG. They are likely radio jets/lobes, whose sizes are ∼10–20 kpc and locations are aligned with X-ray cavities. If we assume that the radio jets/lobes expand with the sound velocity, their ages are estimated to be ∼10 Myr. We also found compact radio emissions near the center and suggest that they are more young bipolar jets ∼1 Myr in age. Moreover, we found extended radio emission surrounding the AGN and discussed the possibility that the component is a product of the cooling flow, by considering synchrotron radiation partially absorbed by molecular clumps, free–free emission from the warm ionized gas, and the spinning dust emission from the dusty circumgalactic medium.